The relationship between serum thyroid hormone levels and symptoms severity in young children with autism - Kopcikova Maria; Raskova Barbara; Belica Ivan; Bakos Jan; Celusakova Hana; Chladna Zuzana; Zibolenova Jana; Ostatnikova Daniela (Endocrine Regulations)
Objective. Autism spectrum disorders (ASD) are neurodevelopmental disorders characterized by impaired social interaction and communication, restrictive and repetitive patterns of behavior, interests and activities. The aim of this study was to determine the postnatal levels of thyroid hormones and investigate their association with the severity of ASD symptoms.